Measuring the Benefits of Employee Engagement - Kumar, V.; Pansari, Anita (MIT Sloan Management Review, 2015)
It's well known that employees' attitudes toward the organization have a significant effect on how they approach their jobs and how they treat customers. But recent research also suggests that high levels of employee engagement are associated with higher rates of profitability growth.